2020
DOI: 10.32731/smq.293.092020.02
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Attributes Impacting Consumer Online Sport Ticket Purchases in a Dual-Market Environment

Abstract: The purpose of the current study was to examine the attributes most influential in consumers’ online ticket buying experiences. Using conjoint analysis, eight scenario profiles were created in order to gauge fan preferences when purchasing sport event tickets online. Attributes included (a) timing of ticket purchase, (b) seating availability, (c) price fluctuations, (d) associated fees, (e) number of pricepoints, (f) fraud risk, and (g) price valuation assessment. Data were collected from 469 attendees at a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(55 citation statements)
references
References 0 publications
2
51
2
Order By: Relevance
“…For example, in Indonesia, when a club decides to rent a stadium, what is taken into consideration is the number of spectators usually because the capacity of the stadium is also directly related to the stadium rental price. Alexander (2001); Popp, Simmons, Shapiro, Greenwell, & McEvoy, (2020) added that distance or place is also a consideration, in addition to ticket prices, because the teams get money from tickets. It does not apply if the audience's travel distance is too far.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Indonesia, when a club decides to rent a stadium, what is taken into consideration is the number of spectators usually because the capacity of the stadium is also directly related to the stadium rental price. Alexander (2001); Popp, Simmons, Shapiro, Greenwell, & McEvoy, (2020) added that distance or place is also a consideration, in addition to ticket prices, because the teams get money from tickets. It does not apply if the audience's travel distance is too far.…”
Section: Discussionmentioning
confidence: 99%
“…However, while sport sales managers do invest heavily in recruitment and initial training and are often able to cite the desired characteristics they seek in job candidates (Popp et al, 2019a;Shreffler et al, 2018), ongoing training may be lacking (Popp et al, 2019c), despite evidence suggesting salespeople who spend a larger percent of their time in professional development activities are significantly more likely to continue working in sales (Pierce et al, 2013). In fact, Popp et al (2017) found nearly a quarter of sales hires in college athletics received fewer than two hours of training before making their first sales call and half of those surveyed received fewer than two hours of monthly ongoing training. Popp et al (2017) also found half of entry-level sales reps received less than two hours of ongoing training per month and only one-third felt their ongoing training was excellent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, Popp et al (2017) found nearly a quarter of sales hires in college athletics received fewer than two hours of training before making their first sales call and half of those surveyed received fewer than two hours of monthly ongoing training. Popp et al (2017) also found half of entry-level sales reps received less than two hours of ongoing training per month and only one-third felt their ongoing training was excellent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, comfort levels with online ticket buying platform attributes, such as trust, convenience, fraud protection or perceived risk and pricing options (including a willingness to pay additional fees) also influence likelihood of Internet-based sport ticket purchases (Ahn et al, 2014;Bauer et al, 2007;Khazaei Pool et al, 2016;Marquez et al, 2020;Popp et al, 2020;Smith et al, 2012). Similar findings have emerged in nonsport ticket purchase settings, such as in the transportation sector among airline (Bigne et al, 2010;Bukhari et al, 2013;Guritno and Siringoringo, 2013) and train (Cheng and Huang, 2013;Mallat et al, 2009;Zalar et al, 2018;Zhao et al, 2016) passengers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For some fans, mobile ticketing technology represents convenience and efficiency, but for others, converting to digital ticket purchases is confusing, frustrating and complicated. Electronic-ticketing purchases for sporting events may induce fears of identity theft and fraud (Popp et al, 2020;Smith et al, 2012). In some recent cases, sport event managers, venue operators and team administrators have made the decision to only allow digital tickets for event entry, eliminating traditional hard tickets or even print-at-home tickets, altogether.…”
Section: Introductionmentioning
confidence: 99%